2004
DOI: 10.1002/cncr.20539
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic hypofractionated high‐dose irradiation for stage I nonsmall cell lung carcinoma

Abstract: BACKGROUND Stereotactic irradiation (STI) has been actively performed using various methods to achieve better local control of Stage I nonsmall cell lung carcinoma (NSCLC) in Japan. The authors retrospectively evaluated results from a Japanese multiinstitutional study. METHODS Patients with Stage I NSCLC (n = 245; median age, 76 years; T1N0M0, n=155; T2N0M0, n=90) were treated with hypofractionated high‐dose STI in 13 institutions. Stereotactic three‐dimensional treatment was performed using noncoplanar dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
438
2
10

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 817 publications
(470 citation statements)
references
References 30 publications
16
438
2
10
Order By: Relevance
“…By comparison, Onishi et al have showed that a BED 100 Gy provided a 92% local control rate for medically inoperable early stage lung cancer in a series with nearly twice the median follow-up (2 years compared with 1.2 years in the present series). 34 The mechanism for this increased radioresistance is not well understood. It is possibly a difference in mean tumor volume between the 2 studies, but it also suggests a more aggressive nature of liver metastases because of selection of more aggressive clonogens capable of metastasizing and forming viable liver tumors.…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, Onishi et al have showed that a BED 100 Gy provided a 92% local control rate for medically inoperable early stage lung cancer in a series with nearly twice the median follow-up (2 years compared with 1.2 years in the present series). 34 The mechanism for this increased radioresistance is not well understood. It is possibly a difference in mean tumor volume between the 2 studies, but it also suggests a more aggressive nature of liver metastases because of selection of more aggressive clonogens capable of metastasizing and forming viable liver tumors.…”
Section: Discussionmentioning
confidence: 99%
“…These data are consistent with that indicating that a BED greater or equal to 100 Gy is necessary to control primary NSCLC. 29,30 One-and 2-year overall survival (OS) rate ranged from 39.7 to 90% and 13 to 53%, respectively, and was largely influenced by the development of widespread distant metastases. However, the selection of patients seemed to have a strong impact on these data, especially with regard to the type of metastasis (isolated vs. not isolated), the state of oligometastatic disease as defined by Hellman and Weichselbaum 10 and the time of onset of the adrenal metastasis (synchronous vs. metachronous).…”
Section: Efficacymentioning
confidence: 99%
“…Recent developments in radiotherapy technology, such as intensity-modulated radiation therapy (IMRT) and three-dimensional (3D) radiotherapy, allow precise energy transfer to the tumor, which has improved local control rates (Onishi et al, 2004;Palazzi et al, 2009). However, the emergence of tolerant cells during or after radiotherapy remains problematic (Peters et al, 1985;Peters et al, 1982).…”
Section: Introductionmentioning
confidence: 99%